PENTINGNYA PENERAPAN KURIKULUM MERDEKA PAUD DALAM MENDORONG PEMBELAJARAN AKTIF DAN BERMAKNA - dia puspita; Loka, Novita (I'tibar: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Education is essential for producing high-caliber people, and the Merdeka Curriculum is being used in Indonesia to raise educational standards, especially in the early childhood education (PAUD) sector. The purpose of this study is to examine how the Merdeka Curriculum is being implemented at PAUD and how it affects meaningful learning. Library research is the methodology, and both deductive and inductive methods are employed to analyze the qualitative data. The findings demonstrate that, in line with children's developmental stages, the Merdeka Curriculum at PAUD places a strong emphasis on experience-based learning strategies and active learning, including learning via play. Through techniques like project-based learning and utilizing the surrounding environment, this teaching methodology also encourages creativity and independence. The perceptual gap between parents and teachers, as well as teachers' limited comprehension and proficiency in implementing more contextual learning strategies, are obstacles, too. To create a learning environment that fosters children's optimal growth, parents, school principals, and instructors must work together. To sum up, the Merdeka Curriculum can produce meaningful learning, but in order to overcome current obstacles, comprehension and competency must be improved. Keyword : Curriculum, Independence, Learning, PAUD